2000
DOI: 10.1097/00000539-200002000-00043
|View full text |Cite|
|
Sign up to set email alerts
|

Ramosetron for Preventing Postoperative Nausea and Vomiting in Women Undergoing Gynecological Surgery

Abstract: This randomized, double-blinded, placebo-controlled trial in 120 women found the effective dose of ramosetron for preventing postoperative nausea and vomiting after gynecological surgery to be 0.3 mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 5 publications
2
29
0
Order By: Relevance
“…[13] Fujii Y e al studied the effect of Ramosetron for preventing postoperative nausea and vomiting in women undergoing gynaecological surgery and also compared Ramosetron and Granisetron for preventing postoperative nausea and vomiting after gynaecologic surgery and concluded that prophylactic therapy with Ramosetron is more effective than Granisetron for the long term prevention of PONV after major gynaecologic surgery. [28] Mild headache, constipation and dizziness have been reported as side effects with all three drugs as was also seen in our study but no serious side effects were seen.…”
Section: Discussionsupporting
confidence: 84%
“…[13] Fujii Y e al studied the effect of Ramosetron for preventing postoperative nausea and vomiting in women undergoing gynaecological surgery and also compared Ramosetron and Granisetron for preventing postoperative nausea and vomiting after gynaecologic surgery and concluded that prophylactic therapy with Ramosetron is more effective than Granisetron for the long term prevention of PONV after major gynaecologic surgery. [28] Mild headache, constipation and dizziness have been reported as side effects with all three drugs as was also seen in our study but no serious side effects were seen.…”
Section: Discussionsupporting
confidence: 84%
“…It has also been shown to be effective for PONV prophylaxis in a dose of 0.3 mg given at the end of surgery (IIIA). 48 COMPARISON BETWEEN THE DIFFERENT 5-HT 3 …”
mentioning
confidence: 99%
“…In addition, the manufacturer's recommended dose is 0.3 mg IV once a day. [21], [22] Therefore, Ramosetron at the 0.3 mg dose was chosen for our study.…”
Section: Discussionmentioning
confidence: 99%